11d-10=6d

Simple and best practice solution for 11d-10=6d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11d-10=6d equation:


Simplifying
11d + -10 = 6d

Reorder the terms:
-10 + 11d = 6d

Solving
-10 + 11d = 6d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-6d' to each side of the equation.
-10 + 11d + -6d = 6d + -6d

Combine like terms: 11d + -6d = 5d
-10 + 5d = 6d + -6d

Combine like terms: 6d + -6d = 0
-10 + 5d = 0

Add '10' to each side of the equation.
-10 + 10 + 5d = 0 + 10

Combine like terms: -10 + 10 = 0
0 + 5d = 0 + 10
5d = 0 + 10

Combine like terms: 0 + 10 = 10
5d = 10

Divide each side by '5'.
d = 2

Simplifying
d = 2

See similar equations:

| N-6n= | | 4m^2n+(-m^2n)=0 | | 4m^2n+(-m^2n)= | | 0.1*x+0.25(5x)=5.25 | | log=0.45 | | 0.85x=612 | | (6x-10)+(6x+10)=18 | | 5(7x+1)=5+2x | | 2(x-7)+3x-1=4x+3 | | 2x+x+9x=3+35+2-4 | | 87b+17b= | | 20x-5x+4=15x-4 | | 25t=25t+5 | | 3x-a=b+a | | -81r+73r= | | g(x)=x^2+22x+12 | | 8x+5=2x-5 | | 7x+6=-12 | | 6a^2+19a+15= | | Y+z=108 | | 8-88n-45n= | | 42=2(x+3)+2(x-12) | | Y=(3x^2-3x+6)*2 | | 2y+3y-5x+2x= | | n+3=q*n | | 42=2(x+3)+(x-12) | | -9(x+2)=16x-3-15x | | -60x^2-77x=0 | | 2[x+1]-1=11forx | | -2x+6y=-18 | | 3(w+4)+3w=32 | | N-2-5-2n= |

Equations solver categories